Hannah Chapman: capstone - Chapman, Hannah, artist (Colorado State University. Libraries, 2018)
The artist's statement: Cyanotype is an alternative process in which rays from the sun expose a layer of photosensitive material on paper or fabric. The marks you see in my cyanotypes are a negative representation of drawings on a transparency. Other processes, like lithography and intaglio, are methods in which an image is etched into the surface of a stone or a metal plate from which multiple impressions can be pulled with the help of ink. Cyanotype and lithography lend themselves to experimental practices in which I am always searching to further immerse my mind. I draw using methods of the automatic and subconscious, as my marks are formed by nothing but instinctual movements and responses to the marks as they come. I do not think about what I draw until I draw it. This way I am tapping into mechanical variations that are programmed into me. The large scale allows me to fall into the act of drawing and presents an inviting quality to the viewer. All of my marks are asking the viewer to witness them. Lack of control and choice are the underlying elements of my work. Chaos is my ultimate inspiration. I did not choose to be me and yet, in all this chaos, I am here. I am here at this moment because of my family (and wonders of the universe). This art is my gratitude. With each piece, my experience and memory expand and my work grows as a celebration of them and the self. The sun burns the spaces surrounding marks and memories. The stone absorbs these marks. What you see are indirect translations of my celebration. My work is a vessel for shadows to exist in the absence of light and space.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking